Antiviral Activity and Adaptive Evolution of Avian Tetherins - Krchlíková, Veronika; Fábryová, Helena; Hron, Tomáš; Young, Janet M; Koslová, Anna; Hejnar, Jiří; Strebel, Klaus; Elleder, Daniel (Journal of virology, 2020)
Tetherin/BST-2 is an antiviral protein that blocks the release of enveloped viral particles by linking them to the membrane of producing cells. At first, BST-2 genes were described only in humans and other mammals. Recent work identified BST-2 orthologs in nonmammalian vertebrates, including birds. Here, we identify the BST-2 sequence in domestic chicken (Gallus gallus) for the first time and demonstrate its activity against avian sarcoma and leukosis virus (ASLV). We generated a BST-2 knockout in chicken cells and showed that BST-2 is a major determinant of an interferon-induced block of ASLV release. Ectopic expression of chicken BST-2 blocks the release of ASLV in chicken cells and of human immunodeficiency virus type 1 (HIV-1) in human cells. Using metabolic labeling and pulse-chase analysis of HIV-1 Gag proteins, we verified that chicken BST-2 blocks the virus at the release stage. Furthermore, we describe BST-2 orthologs in multiple avian species from 12 avian orders. Previously, some of these species were reported to lack BST-2, highlighting the difficulty of identifying sequences of this extremely variable gene. We analyzed BST-2 genes in the avian orders Galliformes and Passeriformes and showed that they evolve under positive selection. This indicates that avian BST-2 is involved in host-virus evolutionary arms races and suggests that BST-2 antagonists exist in some avian viruses. In summary, we show that chicken BST-2 has the potential to act as a restriction factor against ASLV. Characterizing the interaction of avian BST-2 with avian viruses is important in understanding innate antiviral defenses in birds.IMPORTANCE Birds are important hosts of viruses that have the potential to cause zoonotic infections in humans. However, only a few antiviral genes (called viral restriction factors) have been described in birds, mostly because birds lack counterparts of highly studied mammalian restriction factors. Tetherin/BST-2 is a restriction factor, originally described in humans, that blocks the release of newly formed virus particles from infected cells. Recent work identified BST-2 in nonmammalian vertebrate species, including birds. Here, we report the BST-2 sequence in domestic chicken and describe its antiviral activity against a prototypical avian retrovirus, avian sarcoma and leukosis virus (ASLV). We also identify BST-2 genes in multiple avian species and show that they evolve rapidly in birds, which is an important indication of their relevance for antiviral defense. Analysis of avian BST-2 genes will shed light on defense mechanisms against avian viral pathogens.
Keywords: ptačí sarkom; viry ptačího sarkomu; HEK293 buňky; Virus Release; Signal Transduction; replikace viru; molekulární evoluce; HEK293 Cells; buněčné linie; Humans; Passeriformes; Sequence Homology, Amino Acid; Cell Line; sekvenční homologie aminokyselin; zvířata; selekce (genetika); gag Gene Products, Human Immunodeficiency Virus; interakce hostitele a patogenu; regulace genové exprese; genové produkty gag - virus lidské imunodeficience; signální transdukce; Gene Expression Regulation; Virus Replication; Sarcoma, Avian; Avian Proteins; tetherin; Bone Marrow Stromal Antigen 2; Sequence Alignment; antigen stromálních buněk kostní dřeně; sekvence aminokyselin; chicken; uvolnění viru z buňky; restriction factor; sekvenční seřazení; Avian Sarcoma Viruses; avian retrovirus; Selection, Genetic; Evolution, Molecular; Animals; Amino Acid Sequence; lidé; ptačí proteiny; HIV-1; Host-Pathogen Interactions; Galliformes; fibroblasty; Fibroblasts